IDDQ Detectable Bridges in Combinational CMOS Circuits. Issue 3 (1997) - Isern, E.; Figueras, J.
Abstract : Undetectable stuck-at faults in combinational circuits are related to the existence of logic redundancy ( s-redundancy ). Similarly, logically equivalent nodes may cause some bridging faults to become undetectable byI D D Q testing. An efficient method for the identification and removal of such functionally equivalent nodes ( f-redundant nodes ) in combinational circuits is presented. OBDD graphs are used to identify the functional equivalence of candidate to f-redundancy nodes. An f-redundancy removal algorithm based on circuit transformations to improve bridging fault testability, is also proposed. The efficiency of the identification and removal of f-redundancy has been evaluated on a set of benchmark circuits.